A scoping review of emotion regulation and inhibition in emotional eating and binge-eating disorder: what about a continuum? - Arexis, Mahé; Feron, Gilles; Brindisi, Marie-Claude; Billot, Pierre-Édouard; Chambaron, Stéphanie (Journal of eating disorders, 2023)
Emotional eating is defined as a nonpathological eating behavior, whereas binge-eating disorder (BED) is defined as a pathological eating behavior. While different, both share some striking similarities, such as deficits in emotion regulation and inhibition. Previous research has suggested the existence of an "eating continuum" that might reflect the increased severity of overeating behaviors, that is, from nonpathological overeating to BED. The main aims of this scoping review were to explore in the literature the idea of a continuum between emotional eating and BED and to observe whether deficits in emotion regulation and inhibition follow this continuum in terms of severity. The other aims were to hopefully clarify the ill-defined concept of overeating, to question the potential role of positive emotions and to identify potential knowledge gaps. A systematic scoping review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. Two databases (PubMed/Medline and PsycINFO) were examined in complete accordance with the beforehand sharply defined eligibility and exclusion criteria. The main criteria included adults (≥ 18) with emotional eating, BED or overeating and emotion regulation and inhibition as exposure criteria. Thirty-two studies were included in this scoping review. If the results showed a link between emotional eating and BED, with the presence of inhibition and emotion regulation deficits in both eating behaviors, no mention of a continuum between emotional eating and BED was found. In the absence of research directly comparing emotional eating and BED in the same studies and testing the potential increase in severity of emotion regulation and inhibition deficits along this continuum, there is currently no certainty that a continuum exists between emotional eating and BED. In the end, the idea of a continuum in terms of increased severity of overeating and in terms of emotion regulation and inhibition deficits between emotional eating and BED appears to be a gap in knowledge in the literature. This scoping review highlights the need for further research to identify knowledge gaps.